2014
DOI: 10.3389/fnsys.2014.00153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-pharmacological or pharmacological interventions on cognition and brain plasticity of aging individuals

Abstract: Brain aging and aging-related neurodegenerative disorders are major health challenges faced by modern societies. Brain aging is associated with cognitive and functional decline and represents the favourable background for the onset and development of dementia. Brain aging is associated with early and subtle anatomo-functional physiological changes that often precede the appearance of clinical signs of cognitive decline. Neuroimaging approaches unveiled the functional correlates of these alterations and helped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 147 publications
(180 reference statements)
0
29
0
1
Order By: Relevance
“…Using PD patients as an example one argument is that, although these patients are at significant risk for developing MCI and dementia, and although the substantial impact of cognitive dysfunctions on the patients' quality of life is well-documented [3], there is as yet, no pharmacological intervention that can be offered to at risk patients or patients with MCI. Furthermore, CT is known to be effective in healthy elderly [4] and (non-PD) MCI patients [5], and cognitive stimulation is effective in patients with (Alzheimer's and other forms of) dementia [6]. Thus, successful use of CT in PD patients appears feasible.…”
Section: Dear Editormentioning
confidence: 99%
“…Using PD patients as an example one argument is that, although these patients are at significant risk for developing MCI and dementia, and although the substantial impact of cognitive dysfunctions on the patients' quality of life is well-documented [3], there is as yet, no pharmacological intervention that can be offered to at risk patients or patients with MCI. Furthermore, CT is known to be effective in healthy elderly [4] and (non-PD) MCI patients [5], and cognitive stimulation is effective in patients with (Alzheimer's and other forms of) dementia [6]. Thus, successful use of CT in PD patients appears feasible.…”
Section: Dear Editormentioning
confidence: 99%
“…Research suggests the potential and benefits of cognitive intervention and other non-pharmacological approaches in normal age-related cognitive decline and dementia (both at pre-dementia and dementia stages) [12,25,30], leading to hope that these approaches might assist in impeding, minimizing or delaying cognitive dysfunction associated with healthy and unhealthy trajectories of aging.…”
Section: Neuropsychological Effects Of Cognitive Intervention In Aginmentioning
confidence: 99%
“…Additionally, as Pieramico et al [25] point out, neuroimaging advances have led to an improved understanding of functional, spatiotemporal and structural aspects of the brain, as well as consolidated concepts of behavioral plasticity, structural and functional neuroplasticity in the aging brain. Indeed, converging with animal research and human clinical studies, evidence from human neuroimaging studies shows that cognitive intervention leads to neuropsychological improvements and brain changes [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is highly effective in improving memory functions during adulthood in both humans and rodents (reviewed in 2 ). It may be argued that the potency of exercise in preserving and improving cognition may equal or exceed that of any currently existing pharmacological intervention 3 . Preclinical studies using rodent models have identified underlying neurobiological mechanisms by which exercise improves brain, and specifically hippocampal function.…”
Section: Introductionmentioning
confidence: 99%